Variability of Acoustically Evidenced Methane Bubble Emissions Offshore Western Svalbard - Veloso-Alarcon, Mario E.; Jansson, Pär; De Batist, Marc; Minshull, Timothy A.; Westbrook, Graham K.; Pälike, Heiko; Bünz, Stefan; Wright, Ian; Greinert, Jens (Geophysical Research Letters, 2019)
Accepted for publication in Geophysical Research Letters; available at https://doi.org/10.1029/2019GL082750. @2019 American Geophysical Union. Further reproduction or electronic distribution is not permitted. Large reservoirs of methane present in Arctic marine sediments are susceptible to rapid warming, promoting increasing methane emissions. Gas bubbles in the water column can be detected, and flow rates can be quantified using hydroacoustic survey methods, making it possible to monitor spatiotemporal variability. We present methane (CH 4 ) bubble flow rates derived from hydroacoustic data sets acquired during 11 research expeditions to the western Svalbard continental margin (2008–2014). Three seepage areas emit in total 725–1,125 t CH 4 /year, and bubble fluxes are up to 2 kg·m −2 ·year −1 . Bubble fluxes vary between different surveys, but no clear trend can be identified. Flux variability analyses suggest that two areas are geologically interconnected, displaying alternating flow changes. Spatial migration of bubble seepage was observed to follow seasonal changes in the theoretical landward limit of the hydrate stability zone, suggesting that formation/dissociation of shallow hydrates, modulated by bottom water temperatures, influences seafloor bubble release.